Pope Francis: His Life and Thought by Mario I. Aguilar - Lida, Miranda (2015)
The author poses clearly the meaning and goals of his book since its first page:to know and understand Pope Francis beyond his own myth. Aguilar shows us notan extraordinary and audacious pope, but a singular priest who encountered manyobstacles in his long career until he achieved the rank of cardinal during the lastyears of John Paul II?s pontificate. Aguilar knows that the most original aspect ofJorge Mario Bergoglio?s life is the long road he must have traveled to the papacy.His election in a conclave as pontiff had never been in his plans. Nevertheless,when the opportunity arrived, he showed himself fully prepared. Thus, Aguilardoes not focus on Francis?s pontificate; rather, he has chosen to tell us the completestory of Bergoglio?s life before his elevation.